Implementation of Islamic Education Curriculum in Kindergarten in Incorporating Social Concern Values from an Early Age - Aziz, Mursal; Ashshiddiqi, Muhammad Hasbie; Suratni, Suratni (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to examine the implementation of the Islamic education curriculum in instilling social awareness values in early childhood at Hatinia Barokah Kindergarten, North Labuhanbatu. A qualitative descriptive approach was used to gather data through observations, in-depth interviews with teachers and the principal, and documenting learning analysis. The results showed that social values, such as empathy, mutual assistance, and cooperation, are involved in daily activities through habituation methods, such as sharing food, cleaning the environment together, and helping friends. Teachers act as role models who teach these values by providing direct examples in daily social interactions. Furthermore, this study found the importance of collaboration between teachers and parents in strengthening the instillation of social values, which creates a supportive educational environment. Challenges faced include differences in family backgrounds and limited teacher training in social-based character education. This study concluded that despite these challenges, a habituation-based approach and parental involvement can strengthen the implementation of the Islamic education curriculum in shaping children's social character. This research contributes to the development of an early childhood education curriculum based on social values and Islamic character.